Eutirucallin, a RIP-2 Type Lectin from the Latex of Euphorbia tirucalli L. Presents Proinflammatory Properties - Santana, Sanzio Silva (Public Library of Science, 2014)
Lectins are carbohydrate-binding proteins that recognize and modulate physiological activities and have been used as a toll for detection and identification of biomolecules, and therapy of diseases. In this study we have isolated a lectin present in the latex of Euphorbia tirucalli, and named it Eutirucallin. The latex protein extract was subjected to ion exchange chromatography and showed two peaks with haemagglutinating activity. Polypeptides of 32 kDa protein extract strongly interacted with immobilized galactose (α-lactose > D-N-acetylgalactosamine). The Eutirucallin was obtained with a yield of 5.6% using the α-lactose column. The lectin domain has 32 kDa subunits and at least two of which are joined by disulfide bridges. The agglutinating capacity for human erythrocytes A(+), B(+) and O(+) is inhibited by D-galactose. The haemagglutinating activity of Eutirucallin was independent of Ca(2+) and maintained until the temperature of 55°C. Eutirucallin presented biological activities such as neutrophils recruitment and cytokine prodution by macrophages. The analysis of the trypsin-digested Eutirucallin by ms/ms in ESI-Q-TOFF resulted in nine peptides similar to type 2 ribosome-inactivating protein (type-2 RIP). It's partial sequence showed a similarity of 67.4 – 83.1% for the lectin domain of type-2 RIP [Ricin and Abrin (83.1%), Viscumin, Ebulin, Pulchellin, Cinnamomin, Volkensin and type-2 RIP Iris hollandica]. Our data suggest that Eutirucallin is a new member of type 2 ribosome-inactivating protein and presents biotechnological potential.